THE MAIN FACTORS AFFECTING THEDEVELOPMENT OF THE INDUSTRY SECTOR OF THE ECONOMY - Tuychiev Komiljon Lazizovich (Scholar Express Journals, 2023)
The importance and role of the industrial sector in the development of the country's economy are highlighted. The issues of stable development of the industrial sector in the national economy of Uzbekistan, the innovative activity of the industry, as well as the efficiency of management are highlighted. The analysis showed that as a result of the measures taken to reform the economy, a number of positive shifts were achieved in the structural changes implemented in the industrial complex. The main factors were identified. industrial development
Keywords: Industry; factors; efficiency; structural changes